(3LGeY GdCUhd dCMGOjK GdQShds - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3ajg HbjI MQa GdNGA s
(3BNQgG (B:s
(3hjfJgi HMQa GdUGO s
(3GdfSNI HgG MhGTs
(3hgPg GdeLdOI bO Jda BNQgGs
(3hUhQ efgG MJi UaMI (B182s
(3hGdHGbi dGjUdM ddJUhjQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
Keywords: (3GdMOjK h GdeUWdMs